Analisis Sistem Pengendalian Internal Pengelolaan Dana Bantuan Keuangan Khusus (BKK) di Subak Tani Kayupas Beduuran Desa Banyuning - Ketut Suci Artini; I Gede Agus Pertama Yudantara (Jurnal Akuntansi Profesi, 2022)
Abstrack   This study aims to find out the implementation of the internal control system for special financial aid funds management with the Tri Hita Karana concept in Subak Kayupas Beduuran Banyuning Village. This research was conducted by using qualitative method. Data was collected through observation, interviews, and documentation which were subsequently carried out data analysis through three stages, namely (1) data reduction, (2) data presentation, and (3) drawing conclusions. The results of this study showed that the special financial aid funds management in the Subak Kayupas Bedauuran starting from the planning, implementation, and accountability stages had implemented values that are constrained in the concept of Tri Hita Karana, namely Parahyangan, Pawongan, and Palemahan. The implementation of the internal control system based on environmental control components, risk assessment, control activities, information and communication, and monitoring in the management of special financial aid funds accompanied by the concept of Tri Hita Karana in Subak Kayupas Beduuran Banyuning has run quite adequately, so  it can be concluded that special financial fund aid management in Subak Kayupas Beduuran has run well.   Keywords: Subak, Fund Management, Internal Control